Diversity in archaeology : proceedings of the Cambridge Annual Student Archaeology Conference 2020/2021 (Oxford)
xii, 385 sayfa
Keywords: “30 papers explore a wide range of topics such as women’s voices in archaeological discourse; researching race and ethnicity across time; use of diversified science methods in archaeology; critical ethnographic studies; diversity in the archaeology of death, heritage studies, and archaeology of ‘scapes’. Diversity in Archaeology is the result of the fourth Cambridge Annual Student Archaeology Conference (CASA 4), held virtually from January 14-17, 2021. CASA developed out of the Annual Student Archaeology Conference, first held in 2013, which was formed by students at Cambridge, Oxford, Durham and York. In 2017, Cambridge became the home of the conference and the name was changed accordingly. The conference was developed to give students (from undergraduate to PhD candidates) in archaeology and related fields the chance to present their research to a broad audience. The theme for the 2020/2021 conference was Diversity in Archaeology which opened our conference to multiple interpretations, varied presentations and sundry perspectives from different regions of the world. This volume consists of 30 papers which were presented in 7 different sessions. The papers present a great variety in both geography and chronology and explore a wide range of topics such women’s voices in archaeological discourse; researching race and ethnicity across time; use of diversified science methods in archaeology; critical ethnographic studies; diversity in the archaeology of death, heritage studies, archaeology of ‘scapes’ and more.” --